Proceedings of the 4th Nordic Conference on Human-Computer Interaction: Changing Roles 2006
DOI: 10.1145/1182475.1182478
|View full text |Cite
|
Sign up to set email alerts
|

An empirical evaluation of undo mechanisms

Abstract: While various models of undo have been proposed over the years, no empirical study has yet been done to discover which model of undo most closely aligns with what users expect an undo command should do. In this paper, we discuss the results of such a study that compares the ubiquitous linear undo model with two variations of selective undo: script selective and cascading selective. Unlike the script model, cascading selective undo takes into account dependencies between user actions. Our study shows that, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Consequently, their models often allow only one outcome to a user command even when other reasonable responses could be considered. Indeed, studies showed that the users' expectations to non-trivial modifications on history are not always fully consensual [7] and can depend on the platform [16,17]. We illustrate this with two examples.…”
Section: Limited Vocabularymentioning
confidence: 92%
“…Consequently, their models often allow only one outcome to a user command even when other reasonable responses could be considered. Indeed, studies showed that the users' expectations to non-trivial modifications on history are not always fully consensual [7] and can depend on the platform [16,17]. We illustrate this with two examples.…”
Section: Limited Vocabularymentioning
confidence: 92%
“…Whereas early systems using simple dependency models [3,19], later work focused on formal, sound and complete modeling of dependencies, and even automatically cascading the selective undo when necessary for consistency [6]. User studies showed that people could predict and understand what these selective undo systems will do [7]. Whereas in one sense, painting systems do not have such dependencies since all actions operate on pixels, we do study the issue of conflicts when the boundaries of actions overlap, as discussed below.…”
Section: Selective Undomentioning
confidence: 99%
“…The original mechanism [Prakash and Knister 1994] basically removed the command to undo from the history, and then redid the commands that were coming after it in the history. However, this interpretation of the history of commands as a script may not always match users' mental model of the undo command [Cass et al 2006]. With direct selective undo [Berlage 1994], application developers can implement an undo behavior that is more appropriate in this context, by adding an inverse command at the end of the history.…”
Section: Undo Modelsmentioning
confidence: 99%